IDENTIFIKASI MUTASI H63D GEN HFE PADA KELAINAN HBE - Yanuarita Tursinawati; Nyoman Suci Widyastiti; Moedrik Tamam (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
The H63D HFE mutation has been reported to be responsible for primary haemochromatosis. The allele frequency in Indonesianpopulation is about 2.8%. Co inheritance between H63D mutation and hemoglobin disorders such as Thalassemia may increase theseverity of iron overload. Nevertheless, the coinheritance of this mutation with HbE disorder is the most common hemoglobin disorderin Indonesia and the gene frequency have not been reported especially in Javanese ethnic. To identify the presence and the frequency ofH63D HFE mutation in HbE disorder among Javanese ethnic. A cross sectional study involved 24 Javanese individuals who consist of21 HbE heterozygotes (HbAE) and 3 HbE homozygotes (HbEE) subjects. The subjects were screened for H63D mutation by digestion ofPCR products with MbO I restriction endonuclease. The genotype frequency for wt/wt was 95.24% in HbAE, 100% in HbEE and for wt/H63D was 4.76% in HbAE. The allele frequency for H63D HFE mutation was 2.08% in total sample of HbE. The allele frequencies inHbAE and HbEE individual were 2.38% and 0%, respectively. H63D HFE mutation is found in 24 Javanese ethnic individual with HbEdisorder. However, the allele frequency of H63D HFE mutation is low and almost similar to the allele frequency of H63D HFE mutationin Indonesian population.